As relações entre a educação infantil e educação especial: balanço tendencial das dissertações e teses (2013 a 2021) - Sampietri, Carolina Presenza (2023)
The present research aimed to analyze the main trends in research regarding the relationship between early childhood education and special education, as expressed in Brazilian dissertations and theses published in the Catálogo de Teses e Dissertações da Coordenação de Aperfeiçoamento do Pessoal de Ensino Superior (CAPES) "The Catalog of Theses and Dissertations of the Coordination of Superior Level Staff Improvement", under the Ministry of Education (MEC), from 2013 to 2021. Recognizing that this body of work may not represent the most advanced in this field but rather reflects the graduate studies programs where they were defended, we delineated indicators such as institutional origins, geographical locations, themes, focuses, as well as research methodologies employed. This investigation draws upon the contributions of cultural materialism by Raymond Williams (2011), considering the "selective tradition" and the meanings and practices emphasized or excluded in works published during a specific period. It was observed that qualitative research conducted at academic master's level from federal educational institutions in the southeastern region of Brazil predominated. The most addressed thematic area was Educational Practice, encompassing comprehensive studies on both disability and early childhood education, with field research as the primary research approach. Research instruments used included interviews and observations, with teachers and students being the primary sources. Through the investigations conducted in this research, it became possible to comprehend the landscape of Brazilian educational research concerning the relationship between special education and early childhood education, its advancements, and the persistent challenges